Carbon microspheres supported cobalt catalysts for phenol oxidation with peroxymonosulfate - Zhou, Guanliang; Sun, Hongqi; Ang, Ming; Tade, Moses; Wang, Shaobin (CHEMECA, 2014)
In this paper, we report an in-situ method for one-pot synthesis of carbon microspheres supported cobalt catalysts (Co/CMS) by a hydrothermal process, followed by calcination at 300, 400 and 500 oC, respectively. Cobalt would distribute three-dimensionally in the spheres. Many characterization techniques, such as XRD, SEM, EDS and elemental mapping were applied to investigate the physicochemical properties of the supported catalysts. The catalytic activities were evaluated by decomposition of 20 ppm phenol solutions with sulfate radicals. It was found that the Co/CMS catalysts were able to efficiently decompose phenol by activation of PMS. Co/CMS-300, 400 and 500 can completely decompose 20 ppm phenol in 15, 5 and 10 min, respectively. Kinetics studies were carried out to investigate the effects of catalyst loading, PMS amount, and reaction temperature on phenol degradation efficiency. Deactivation and regeneration were also discussed.